Possibilty of the lower third molar eruption: Radiographic analysis - Nedeljković Nenad; Stamenković Zorana; Tatić Zoran; Račić Alek (Vojnosanitetski Pregled)
Backgraund/Aim. To assess the possibility of the eruption of the lower third molar on the basis of the measured parameters: retromolar space, mesiodistal crown width of a molar and the third molar angulation. Methods. The investigation included 104 patients both sexes (43 boys, and 61 girls), 16 to 25 years old (meanage, 18 years). It was performed using the orthopanthomographic radiographs analysis of those patients. Each radiograph was covered by tracing paper, and the contoures of the followiny anatomic details were drawn: a) the crown and root contours of third molars, upper and lower central incisors, distal molars in occlusion, anterior edge of ramus mandible, b) lines: 1. the occlusal plane, 2. the line of retromolar space, 3. the mesiodistal crown width of third molar, 4. the axial shaft of the third molar and the distal angle between occlusal plane and the axial shaft of the third molar. The values were measured with an orthodontic caliper: the diameter of retromolar space, diameter of mesiodistal width, the value of distal angle between occlusal plane and axial shaft of molar. Results. A favourable angulation of the lower third molar (more than 60°) was found in, boys (left 27.90%, right 32.55%), girls (left 39.34%, right 37.77%). A favourable relationship between the diameters of mesiodistal width of the third molar and retromolar space was found in, boys, (left 13.59%, right 16.27%), girls, (left 8.19%, right 14.75%). A favorable relationship between the diameters of mesiodistal width of the third molar and the retromolar space and the angulation was found in boys, (left 9.30%, right 11.62%), girls, (left 6.56%, right 9.83%). Conclusion. There was not any statistically significant difference found between the relation of the retromolar value, third molar mesiodistal diameter, or of the third molar angulation to the left and the right side nor of their mutual relations in comparing boys and girls. A favorable prognosis was found in 9.33% of the patients.